Intermediary multicentric prospective and comparative analysis of 435 Mobile bearing Total Knee Arthroplasties of Ultra Congruent stabilization mechanism versus Peg and Cam stabilization mechanism A point-in-time analysis of the OrthowaveTM6 database - Durand, J.M.; Viale, P.; Massin, P.; Cotte, J.L.; Jardin, C. (TERRA ORTHOPAEDICA, 2020)
The Rolflex TONIC total knee implant was launched in early 2016. It is a cruciate sacrificing design and offers a choice of 2 cruciate substituting mechanism according to the UC (Ultra-Congruent) concept or to the PS (Postero-stabilisation with peg and cam) concept. The PS choice can be associated to a fixed tibial bearing or to a mobile tibial bearing, while the UC choice can only be associated to a mobile tibial bearing. The international use of UC total knee prosthesis is low: according to the 2019 AJRR report the UC variant was up at 4.5% of use in 2018, while the PS variant accounted for the largest frequency of use at 51.6%. The second most used type of TKA was the cruciate retaining (CR) variant at 43.8% of use. There is currently no CR variant in the Rolflex TONIC portfolio.In order to inform of any differences in terms of etiology, indications, patient profile, surgical choices, and clinical and functional performance between the PS and the UC cruciate substituting mechanisms, this document will analyze only the mobile bearing variants of the Roflex TONIC UC and PS. The patients implanted with Fixed bearing PS will not be included in this analysis.A prospective clinical follow-up of the Rolflex TONIC has been organized by the sponsor (Evolutis, Briennon, France) to evaluate the safety and performance of this new device. This study includes the implants used since June 2016 and up to December 2018. The study design will review the patients at 2, 5 and 10 years of follow-up. At the date of this intermediary report, the 2 years review is not yet terminated. The 2 years report is expected for early 2021 when all patients included will show more than 2 years of FU. Therefore, this intermediary analysis should only be viewed as a security control analysis in search for any anticipated deviation in the expected results. The average length of follow- up will remain short until all patients will be reviewed at 2 years of minimal FU, yet it will evidence if any short or mid-term complication occurred, and how good is the recovery of the patients estimated through an IKS and an OXFORD scores.